Caracterização da demanda metabólica, aspectos termorregulatórios e da carga interna de treinamentos técnico-táticos de futsal profissional - Carolina Franco Wilke (2013)
This study aimed to characterize the metabolic and thermoregulatory demand and the internal load, and to investigate the association between TRIMP and session RPE in professional futsal training. The 12 players from a professional futsal team who volunteered for the studyperformed a maximal incremental exercise to determine VO2max, HRmax, HR at the VT and RCP and the individual relationship between HR and VO2 prior to the experimental sessions. In all technical-tactical training sessions performed during 8 weeks, the players HR wasmeasured continuously, RPE was measured between 15 and 20 minutes after the end of the session, body mass was measured before and after training, and volume of fluid intake was measured after each session. TRIMP (LUCIA et al., 2003), session RPE (Foster et al., 1996),sweat rate and percentage of body mass reduction were calculated for each player in each session. Intensity of different activities (4x4, 6x4 and game simulation) was also calculated. The average training intensity was 74 ± 4% of HRmax, corresponding to 9.3 kcal / h and 7.7 METs. The players kept high intensity on 20 ± 8% of total training time, moderate in 28 ± 6% and low in 51 ± 10%. There was no difference in the intensity of 4x4, 6x4 and game simulation activities. The average daily TRIMP was 153 ± 21 AU and total TRIMP was 531 ± 148 UA. The average daily session RPE was 448 ± 92 UA, while total session RPE was 1858± 543 UA. We observed a moderate correlation (r = 0.71, p <0.001) between the daily mean TRIMP and session RPE, however only four athletes showed significant individual correlation, and no correlation was found between RPE and the average intensity of the sessions evaluated. Mean sweat rate, total volume of liquid ingested, and percentage of bodymass reduction were 1.13 ± 0.53 L / h, 1.32 ± 0.20 L and 0.52 ± 0.19%, respectively. Thus, professional futsal technical-tactical training sessions have specific demand to the game, and the players present little percentage of body mass reduction. Moreover, session RPE is aninteresting tool for monitoring training, but does not replace the HR measurement and its interpretation should be made individually.